2021
DOI: 10.1186/s13690-021-00554-y
|View full text |Cite
|
Sign up to set email alerts
|

Maternal healthcare utilization and full immunization coverage among 12–23 months children in Benin: a cross sectional study using population-based data

Abstract: Background Maternal and child health are important issues for global health policy, and the past three decades have seen a significant progress in maternal and child healthcare worldwide. Immunization is a critical, efficient, and cost-effective public health intervention for newborns. However, studies on these health-promoting indicators in low-income and middle-income countries, especially in sub-Sahara Africa are sparse. We investigated the association between maternal healthcare utilization… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
13
3
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 37 publications
6
13
3
1
Order By: Relevance
“…It may be because of the cultural beliefs of the communities who feel safer at home during childbirth [ 32 ]. In contrary to the studies suggesting a positive correlation between SBA and immunization [ 33 , 34 ], immunization coverage was higher in children assisted by TBA in this study. As suggested previously [ 21 , 35 ], tetanus immunization taken during pregnancy was significantly associated with child immunization coverage.…”
Section: Discussioncontrasting
confidence: 99%
“…It may be because of the cultural beliefs of the communities who feel safer at home during childbirth [ 32 ]. In contrary to the studies suggesting a positive correlation between SBA and immunization [ 33 , 34 ], immunization coverage was higher in children assisted by TBA in this study. As suggested previously [ 21 , 35 ], tetanus immunization taken during pregnancy was significantly associated with child immunization coverage.…”
Section: Discussioncontrasting
confidence: 99%
“…This study is supported by a study conducted in Benin that reported mothers who had early PNC were more likely to use maternal and child health services. 28 …”
Section: Discussionmentioning
confidence: 99%
“…The result was in line with previous reports. 13 , 59 , 60 Maternal and child health care are interrelated. The more women adhere to maternal and child care, the more women know benefit, understand the appointment and improved communication with care providers.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies reported the opposite. 13,57,59,60,[63][64][65] Institutional deliveries advantage for further maternal and childcare is not questionable. However, the inability of caregivers to transition from delivery services and to later continue with care provided for their children is a major concern in sub-Saharan Africa.…”
mentioning
confidence: 99%